Modern Food Microbiology (6th Edition) - Jay, James M. (Aspen Publishers, 2011)
Explores the fundamental elements affecting the presence, activity, and control of microorganisms in food. Incorporates the key subjects required to meet the minimum standards for degrees in food science with a wealth of practical information about the most essential factors and principles that affect microorganisms in food.